Genome-wide identification and analysis of the NF-Y transcription factor family reveal its potential roles in tobacco (Nicotiana tabacum L.) - Zhen Tian; Luyao Xue; Jincun Fu; Wenting Song; Baojian Wang; Jinhao Sun; Xiujiang Yue; Fanrui Cheng; Jingjing Mao; Jiangtao Chao; Dawei Wang; Shaopeng Li (Plant Signaling & Behavior)
Nuclear Factor Y (NF-Y) represents a group of transcription factors commonly present in higher eukaryotes, typically consisting of three subunits: NF-YA, NF-YB, and NF-YC. They play crucial roles in the embryonic development, photosynthesis, flowering, abiotic stress responses, and other essential processes in plants. To better understand the genome-wide NF-Y domain-containing proteins, the protein physicochemical properties, chromosomal localization, synteny, phylogenetic relationships, genomic structure, promoter cis-elements, and protein interaction network of NtNF-Ys in tobacco (Nicotiana tabacum L.) were systematically analyzed. In this study, we identified 58 NtNF-Ys in tobacco, respectively, and divided into three subfamilies corresponding to their phylogenetic relationships. Their tissue specificity and expression pattern analyses for leaf development, drought and saline-alkali stress, and ABA response were carried out using RNA-seq or qRT-PCR. These findings illuminate the role of NtNF-Ys in regulating plant leaf development, drought and saline-alkali stress tolerance, and ABA response. This study offers new insights to enhance our understanding of the roles of NtNF-Ys and identify potential genes involved in leaf development, as well as drought and saline-alkali stress tolerance of plants.